Multicultural Counselling to Restore Social Harmony in a Multiethnic Acehnese Community - Kamsani, Siti Rozaina; Sinring, Abdullah; Fitri, Mutia; Nuraida, Nuraida; Yacob, Fakhri (Jurnal Ilmiah Peuradeun, 2025)
This study examines the effectiveness of group-based multicultural counseling integrated with Participatory Action Research (PAR) in restoring social cohesion within a post-conflict multiethnic community in Gampong Wonosari, Aceh. The research aimed to design, implement, and evaluate a counseling model that addresses persistent polarization between Javanese and Gayo communities. A PAR design with two intervention cycles was employed, each consisting of planning, counseling sessions, observation, and collaborative reflection. Fourteen purposively selected participants (8 Javanese and 6 Gayo) were involved, screened using the Multicultural Social Relation Vulnerability Questionnaire (MSRVQ). Data collection combined the Multicultural Social Relation Observation Sheet (MSROS), reflection notes, and thematic analysis using NVivo, while quantitative changes were tested with the Wilcoxon signed-rank test and effect size calculation. Results demonstrated a significant improvement in interethnic relations: the overall empowerment score increased from 54.54% in Cycle I to 72.07% in Cycle II, with individual scores rising from 62.50% to 73.89% (Z = –2.94, p < 0.01, r = 0.65). Qualitative findings supported these outcomes, showing enhanced empathy, greater openness, and increased confidence in intercultural interactions. This study contributes theoretically by contextualizing Social Learning Theory and the Contact Hypothesis in rural post-conflict communities and methodologically by integrating PAR with mixed-methods counseling interventions. Practically, it provides a replicable model for policymakers, educators, and civil society organizations to strengthen social cohesion in plural societies beyond Aceh.